Untold Story: Water Source Problem of Barangay Cagangohan, Panabo City, Philippines - Onabia, Divine S.; Arcena, Rosemarie B.; Laguna, Kris Jean L.; Allawan, Jovany Gleen L. (Journal of Health Science and Medical Therapy, 2024)
This research aimed to determine the lived experiences of the parents in Barangay Cagangohan, Panabo City, Davao del Norte, Philippines related to water pollution. The participants were selected through purposive sampling by choosing six respondents. The phenomenological research approach was employed in this study to get their views from their experiences, some of their alternative solutions, and the insights they have gained in facing the problem. Further conclusions can be drawn from the findings about how parents are able to find alternative ways to maintain the health of their families despite the lack of clean water in the community. This result may be used by the government, educators, parents, students, and future researchers as a foundation for offering suggestions and solutions for mitigating the problem of a lack of water sources in the community.